Development and implementation of an itinerant satellite Internet access station for the Inca Trail in Cusco-Machu Picchu - Perú - David Chavez Muñoz, P.; Auccapuri, D.; Paco Fernandez, J.P.; Ronald Pacheco Jurado, Y.; Guadalupe, J.A. (Latin American and Caribbean Consortium of Engineering Institutions, 2024)
This paper presents the design and implementation of a portable satellite station (Ku band) for itinerant multimodal Internet access, to be used on the Inca Trail route to the citadel of Machupicchu – Cusco – Perú. A restrictive and challenging set of requirements had to be meet or exceeded such as low energy consumption, portability and ease of deployment, all of them achieved via a field-tested prototype based on a simple but innovative approach.
Keywords: Satellite; The Internet; Computer science; Telecommunications; Meteorology; Remote sensing; Geography; World Wide Web; Engineering; Aerospace engineering; https://purl.org/pe-repo/ocde/ford#2.03.04